Effect verification of external factor to readability of RFID transponder using least square method. (December 2016) - Balog, Michal; Szilágyi, Erik; Dupláková, Darina; Minďaš, Miroslav
Highlights: Verification of RFID transponder and his qualitative properties by using regression analysis and experiments. Reading rate and total counts evaluation of the RFID transponder by the action of temperature influence. Utilization of regression analysis to determine the next course of behaviour studied transponder. Statistical verification of the written regression model correctness. Abstract: RFID technology is currently one of the most progressively growing identification technologies. It provides a huge potential of use in various fields of industry. The positive impact of its implementation can be monitored also by the rationalization of processes and it became the main basis for the concept of Industry 4.0 for this reason. The article concerns the experimental verification of qualitative properties of the RFID transponder by using regression analysis and experiment in laboratory conditions of expert laboratory. On the basis of experimental measurements, they were created regression models of the impact of external factors acting on the readability of the RFID transponder. The main objective of this study is to present the results of mathematical and statistical approach for verification the declared properties of the RFID transponder are which intended to serve as a basis for implementation of the proposed system into real conditions of the practice.